Influence of Airflow Rate and Stimulus Concentration on Olfactory Event-Related Potentials (OERP) in Humans. (14th November 2017) - Han, Pengfei; Schriever, Valentin A; Peters, Per; Olze, Heidi; Uecker, Florian C; Hummel, Thomas
Abstract: Although the association between odor concentration and olfactory event-related potential (OERP) has been studied, less is known about the influence of airflow on OERP. The aim of this study was to investigate the influence of airflow rate and stimulus concentration on OERP in humans. Electroencephalogram data were collected from young healthy volunteers ( n = 17) in separate sessions where 2-phenylethanol (PEA) was delivered in the following conditions: 8 L/min 50% v/v, 8 L/min 30% v/v, 4 L/min 100% v/v, and 4 L/min 60%v/v. Odor concentrations are referred to the %v/v achieved with air dilution and was not measured in the nose. Odor intensity ratings were recorded immediately after stimulus presentation. Data recorded at 5 electrodes (Fz, Cz, Pz, C3, and C4) were pooled and analyzed using both time-domain averaging and single-trial time–frequency domain approaches. Higher airflow rate significantly increased intensity ratings ( F = 10.98, P < 0.01), and improved the signal-to-noise-ratio ( F = 5.42, P = 0.025). Results from time–frequency analysis showed higher concentration versus lower concentration increased brain oscillations in the slow frequency band (1–3 Hz) at 0–600 ms; while higher airflow rates versus lower airflow rate increased theta-band oscillations (300–600 ms and 5–9 Hz) and decreased delta-band oscillations at 900–1500 ms after stimulus onset. In conclusion, compared to stimulus concentration, airflow rate was associated with improved OERP quality and more pronounced responses. The results suggest that intensity ratings and OERP are strongly related to the steepness of stimulus onset. High airflow rates are suggested for odor delivery in order to record OERP.